The role of crisis management and its relationship to the level of crime during the Corona pandemic from the point of view of students of the Department of Planning and Educational Administration, Faculty of Arts - Sebha University (Journal of Human Sciences, 2022)
The current research aims to identify the role of crisis management and its relationship to the level of crime during the Corona pandemic from the point of view of the students of the Department of Planning and Educational Administration, Faculty of Arts - Sebha University, to identify how crises are managed in the city of Sebha (Corona as a model), the research included a sample of (50) male and female students , was chosen in the style of an organized random sample, the researcher followed the descriptive analytical approach, the results of the research concluded: There is a positive correlation between crisis management and the level of crime during the Corona pandemic from the point of view of the students of the Department of Educational Planning and Management, there are no statistically significant differences between crisis management and the level of The rise in crime during the Corona pandemic according to the gender variable, there are no statistically significant differences between crisis management and the level of crime during the Corona pandemic in the axis (imposing quarantine) and (frequent assault and theft), and there are differences between crisis management and the level of high crime during the Corona pandemic in The axis (the college's dealing with crises) and (the absence of the role of the family) and the tool as a whole according to the age variable, and these differences are in favor of students who reach (23 and above). There are no statistically significant differences between crisis management and the level of crime high during the Corona pandemic in the axis (imposing quarantine), (the frequency of assault and theft) and (the college’s dealing with crises), and there are differences between crisis management and the level of crime during the Corona pandemic in (the absence of The role of the family) and the tool as a whole, and these differences are in favor of the students of the semester (third - fourth) and quarterly (seventh - eighth), there are no statistically significant differences between crisis management and the level of crime high during the Corona pandemic according to the variable of housing type)